Em busca de autoconhecimento e amadurecimento: narrativas de peregrinações à Índia - Bastos, Cecilia Guimarães (Ilha Revista de Antropologia, 2021)
This article analyses two pilgrimage journeys to India in 2007 and 2010 taken by a group of Vedanta students from Rio de Janeiro. It is described, through their narratives, the experiences and interpretations given by the group to these events. In a second instance, the significances and meanings ascribed to these pilgrimages are observed according to the premise that tourism as well as pilgrimage should be understood as travel modalities that hold actions and practices which are related and therefore their terms overlap and their borders superimpose. I understand such categories as able to encompass contrasting discourses as individuals reflect on their experiences and by so doing add meanings to their lives.<br